SISTEM PREDIKSI JUMLAH PENGUNJUNG WISATA WEGO KEC.SUGIO KAB.LAMONGAN MENGGUNAKAN METODE FUZZY TIME SERIES - Fitri Rohmawati; M Ghofar Rohman; Siti Mujilahwati (Joutica, 2017)
Lamongan Regency has enormous potential in tourism development. The need for tourist attractions in Lamongan Regency is in great demand makes the government certainly needs to observe it, the government in this case refers to the Tourism Departmentin Lamongan Regency to maintain and take care of these tourist attractions in order to provide comfort for the visitors. Realized or not, the number of visitors who come to a tourist attraction depends on the convenience of the place for the visitors.Wegois one of the tourist attractions in Lamongan Regency that is very potential in an effort to increase the economic growth in Lamongan Regency that should get the special attention.The rate of tourists who visit Wego increases on certain days.Seeing that potential, the professional handling by the manager of the tourist attraction must be done in an effort to achieve the target company. Related to the problem, then the manager must be able to predict and set the target number of Wego tourist attraction’s visitors for the next period.